Treatment of the Refractory Atrophic Humeral Nonunion with Autogenous Block Iliac Crest Graft and Spongioplasty: a Retrospective Study - Ozdemir, G; Bingol, O; Inci, F; Ceyhan, E; Karahan, N; Deveci, A (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2022)
PURPOSE OF THE STUDY Most humeral nonunions can be successfully treated with a single procedure, but some are more difficult to heal. Humeral nonunions which have two or more surgical procedures were defined as refractory humeral nonunions, and this condition is a very challenging condition. The aim of the study is to show the results of atrophic refractory humeral nonunion treated with open reduction and internal fixation and autogenous block iliac crest graft and spongioplasty. MATERIAL AND METHODS Refractory humeral nonunions treated with open reduction and internal fixation and autogenous block iliac crest graft and spongioplasty from January 2010 to March 2019 were included this study retrospectively. Patient baseline information, number of previous surgeries, comorbidities, follow-up time, fracture union time, and complications were recorded. The functional outcome was evaluated with the Constant scores and Mayo scores at the end of the first year. The primary outcome variable was mentioned as bony union. RESULTS A total of 13 refractory humeral nonunions included this study. The average age of the patients was 50.92±15.55 years (range, 26-78 years), and 8 of them were female. Preoperative and postoperative mean Mayo scores were; 56.54±17.84, and 85.38±7.49 respectively (p<0.001). Preoperative and postoperative mean Constant scores were; 45±11.71, and 80.62±5.38 respectively (p<0.001). DISCUSSION The strict application of basic nonunion principles can result in successful salvage of refractory humeral nonunions. But this concept may not provide sufficient solution for each situation. On the other hand, we also applied the basic nonunion principles. Compression plating and autogenous bone grafting and spongioplasty have been considered as the gold standard in the management of humeral shaft nonunion. CONCLUSIONS Open reduction and internal fixation and autogenous block iliac crest graft and spongioplasty should be considered as an alternative for the treatment of refractory atrophic humeral nonunions, whose treatment is a very challenging condition for surgeons. Key words: block graft, bone grafting, nonunion, refractory humeral nonunion, spongioplasty.
Keywords: transplantace kostí; Fracture Fixation, Internal; Humerus; Humans; os ilium; lidé středního věku; Fractures, Ununited; Fracture Healing; Female; Aged; dospělí; Humeral Fractures; výsledek terapie; senioři; lidé; fraktury humeru; humerus; hojení fraktur; Ilium; vnitřní fixace fraktury; Adult; ženské pohlaví; Bone Plates; kostní destičky; Male; Middle Aged; Retrospective Studies; Treatment Outcome; retrospektivní studie; mužské pohlaví; nezhojené fraktury; Bone Transplantation